2022
DOI: 10.1002/hsr2.925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inpatient experiences on patient satisfaction and the willingness to recommend a hospital: The mediating role of patient satisfaction: A cross‐sectional study

Abstract: Background and Aims As high‐quality health care encompasses patient‐centered care, this study used the perceived quality−satisfaction−behavioral intention and structure‐process‐outcome models to (1) investigate the relationships among patient experience, patient satisfaction, and the willingness to recommend a hospital and (2) estimate the indirect effects of patient satisfaction on the relationship between patient experience and the willingness to recommend a hospital. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Similarly, Park et al [30] showed that PX could be used as an indicator to measure patient satisfaction and loyalty.…”
Section: Acknowledging Patients' Experiences and Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Park et al [30] showed that PX could be used as an indicator to measure patient satisfaction and loyalty.…”
Section: Acknowledging Patients' Experiences and Preferencesmentioning
confidence: 99%
“…It provides a better understanding of healthcare quality and has been integrated into multiple frameworks to depict the expectations of both internal [27] and external healthcare consumers [30].…”
Section: Acknowledging Patients' Experiences and Preferencesmentioning
confidence: 99%
“…Xisfingi and Vozikis (2016) found patient satisfaction and quality of health services. Park et al (2022) found that patient experience directly influences patient satisfaction, and the intention to recommend a hospital. However, patient satisfaction has an indirect effect on the relationship between experience and willingness to recommend a hospital.…”
Section: Hypothesis 1 Service Quality Affects Hospital Patient Satisf...mentioning
confidence: 99%
“…Hypothesis 2. Patient trust has a significant effect on patient satisfaction High-quality health care includes patient-focused care and influences perceived satisfaction and behavior by Park et al (2022) and Rohit (2016). Healthy culture is defined as changing bad habits to be positive.…”
Section: Hypothesis 1 Service Quality Affects Hospital Patient Satisf...mentioning
confidence: 99%
“…In fact, Magnet accreditation is significantly linked to higher HCAHPS scores [21]. Similarly, a Korean study showed that patients who had a good experience at the hospital were more likely to be satisfied and are more willing to recommend the hospital [22]. As such, hospitals ought to be looking at ways to quantify satisfaction and increase it.…”
Section: Introductionmentioning
confidence: 99%